2021
DOI: 10.32628/ijsrst218539
|View full text |Cite
|
Sign up to set email alerts
|

Women's Satisfaction with Maternal care in Ghana : The Doctor's Behaviour as a Regulating Factor

Abstract: <p>The key element of human rights and the road to equity and dignity of women and children is the quality of care received. The provision of maternal health care is based on quality during pregnancy, and distinctly forty-eight hours after delivery, is an important contribution to saving women’s lives and preventing disabilities (Quah, 2016). Thus, the understanding of women's experiences and expectations through the continuum of prenatal care, delivery care and postnatal care is important for assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Similarly, Sandovski et al reported that women are generally satisfied with the care received from morning staff compared with afternoon and night staff [ 32 ] as explored in our study. In another study in Ghana, it was found that clients’ satisfaction in maternal care was linked to how thorough they were examined, and how they were treated with courtesy and respect [ 33 ]. Also, another study in Ghana determined that patients expressed their dissatisfaction at the poor attitudes towards work and poor conditions of some logistics [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sandovski et al reported that women are generally satisfied with the care received from morning staff compared with afternoon and night staff [ 32 ] as explored in our study. In another study in Ghana, it was found that clients’ satisfaction in maternal care was linked to how thorough they were examined, and how they were treated with courtesy and respect [ 33 ]. Also, another study in Ghana determined that patients expressed their dissatisfaction at the poor attitudes towards work and poor conditions of some logistics [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal care is the entrance point for pregnant women, which obtain a wide range of health issues and preventive health services [6]. Several studies reported that the reasons for not attending antenatal classes were lack of transportation, language barriers, and negative perceptions about the type of information provided, and these affected the satisfaction outcomes of foreigners [47].…”
Section: Delivery Outcomesmentioning
confidence: 99%
“…Since the number of pregnant foreign women grows, cultural and linguistic issues make it difficult for them to obtain the care they require, as they are frequently misinterpreted [5]. The availability, use, and successful execution of important labor and delivery treatments are all linked to good pregnancy and childbirth outcomes [6].…”
Section: Introductionmentioning
confidence: 99%